Image Сlustering Method on FPGA - Чумак, В. С.; Tsivinskyi, V. (MC&FPGA, 2023)
This study examines the method of clustering in image processing algorithms implemented on programmable logic integrated circuits (FPGAs). The main steps of developing a clustering algorithm are considered, and the choice of clustering approach is justified. Additionally, the steps for analyzing the results obtained from image processing using this method are discussed.
Keywords: clustering method; FPGA; image processing; k-means